DNA Double Strand Breaks Occur Independent of AID in Hypermutating Ig Genes. Issue 2 (2003) - Bross, Linda; Jacobs, Heinz
Abstract : Somatic hypermutation (SHM) and class switch recombination (CSR) take place in B cells of the germinal center (GC) and are associated with DNA double-strand breaks (DNA-DSBs). Transcription favors the generation of DNA-DSBs in the V-regions and switch regions of Ig genes. Both SHM and CSR are controlled by the Activation Induced Cytidine Deaminase (AID), an enzyme exclusively expressed in B cells of the GC. Because AID is capable of deaminating deoxy-cytidine (dC) to deoxy-uracil (dU), it might directly induce nicks (single strand DNA breaks) and also DNA-DSBs via a U-DNA glycosylase mediated base excision repair pathway ('DNA-substrate model'). Alternatively, AID could function like its closest homologue Apobec-1 as a catalytic subunit of a RNA editing holoenzyme ('RNA-substrate model'). To determine whether AID lies upstream or downstream of the DNA lesions found in hypermutating Ig genes, we have analysed the Vλ locus of AID proficient and AID deficient GC B cells for the presence of DNA-DSBs. Although rearranged Vλ genes are preferred targets of SHM we find that AID-proficient and -deficient Vλ1/2-expressing GC B cells display a similar frequency, distribution and sequence preference of DNA-DSBs in rearranged and germline Vλ genes, favoring the idea that AID acts downstream of the DNA lesions to mediate error prone processing.